The Effect of Biotic and Physical Environmental Factors on Total Individual of Rafflesia meijerii in Batang Gadis National Park - Simamora, Jhon Marthali; Hikmat, Agus; Zuhud, Ervizal A. M. (Department of Forest Resources Conservation and Ecotourism - IPB University, 2017)
Rafflesia meijerii was found in 2004 in Batang Gadis National Park. It was a new species of the genus Rafflesia and endemic in North Sumatra. The purpose of this study was to analyze the biotic and physical environmental factors that affect the habitat quality and the individual numbers of of R. meijerii at the research sites. Data were collected by purposive sampling method with a plot size of 0,1 hectare. The collected data such as: total of R. meijerii, total and species of vegetation, and physical environment factors. Fourty three R. meijerii was found at the sites. Fourty three individuals of R. meijerii were found in February 2016. Quercus gameliflora was dominant in tree and sapling with IVI 33,72% and 55,83% and Selaginella wildenovii was dominant in seedling and ground cover species. Sixty three individuals of Tetrastigma papillosum were found. The results of the ecological factor analysis showed that each of ecological factors did not significantly affect the numbers of R. meijerii (sig. 0,1009> 0,05). Keywords: affect, analyze, conservation, endemic, meijerii